PENGUJIAN FAMA & FRENCH FIVE-FACTORS ASSET PRICING MODEL PADA INDEKS LQ 45 PERIODE 2014-2018 - Putra, Ivan Gumilar Sambas; Susanti, Neneng; Putra, Okta Eka (BISMA: Jurnal Bisnis dan Manajemen, 2019)
This study aims to determine whether the Fama & French Five-Factors Asset Pricing Model can explain the excess return expected by investors. The population used is the LQ 45 index with large capitalization and liquid. Based on the sample in this study was used by 25 companies. The sampling technique used was purposive sampling and the analysis technique used was multiple regression analysis. The results show that the variables in the Fama & French Five-Factors Asset Pricing Model have a significant effect on the excess return, which is 65.7%. Partial testing results also show that all variables in this study have a significant effect on excess return. This means that the Fama & French Five-Factors Asset Pricing Model in this study period can explain the expected rate of return of shares by investors.